Portulaca almeviae (Portulacaceae), a new species from the Pacific coast of Mexico - Ocampo, Gilberto (Phytotaxa, 2019)
Portulaca almeviae (Portulacaceae) is described as a new species from a small area in the Pacific coast of the Mexican State of Jalisco. This is a perennial species growing in a rocky habitat and has thick roots and erect to decumbent stems that can produce adventitious roots at the nodes. One of the most notorious features of this species are the long, abundant white leaf axillary hairs, that can reach up to 15 mm long, a very rare character found in Mexican taxa. Phylogenetic analysis places P. almeviae within the Pilosa clade, close related to P. pilosa samples and other Mexican endemic species.